Traditions of the Magi : Zoroastrianism in Greek and Latin literature - Jong, Albert de, 1966- (Religions in the Graeco-Roman World, 1997)
This is the first full treatment of the Greek and Latin references to Zoroastrianism since the pioneering works of Benveniste, Bidez andamp; Cumont, and Clemen. It focuses on the possibilities offered by the classical reports on Zoroastrianism to reconstruct the history of that faith. The book is divided into three sections. The first section deals with introductory problems concerning ancient religious ethnography and current views of the history of Zoroastrianism. The second section consists of commentaries on five selected passages. The third section offers a thematical overview of the materials and their relevance for the history of Iranian religions. Apart from offering introductions to a wide range of debates and topics in Classics and Iranian studies, the book aims to illustrate the diversity of beliefs and practices in ancient Zoroastrianism.